Prostate Cancer Incidence and Mortality: Global Status and Temporal Trends in 89 Countries From 2000 to 2019 - Wang, Le; Lu, Bin; He, Mengjie; Wang, Youqing; Wang, Zongping; Du, Lingbin (Frontiers in Public Health, 2022)
Aims To evaluate current status of prostate cancer incidence and mortality worldwide, and compare the global trends of incidence and mortality in the past two decades and in the most recent period. Methods Data on the incidence and mortality of prostate cancer for 174 countries in 2020 were obtained from the GLOBOCAN 2020 database, and associations with the human development index (HDI) were evaluated. Data for trend analyses in 89 countries from 2000 to 2019 were retrieved from the Global Burden of Disease 2019 platform. Age standardized incidence rate (ASIR) and mortality rate (ASMR) were calculated by using the Segi's population. The average annual percent changes (AAPC) of ASIRs and ASMRs were evaluated by joinpoint regression analysis. Results A total of 1 414 259 new cases of prostate cancer and 375 304 related deaths were reported in 2020 globally. HDI was positively correlated with ASIRs (P < 0.001) and negatively correlated with ASMRs (P < 0.001). In the past two decades, ASIRs have been increasing in 65 countries, stable in 15 countries and decreasing in 9 countries, and ASMRs have been increasing in 19 countries, stable in 25 countries and decreasing in 45 countries, respectively. In the most recent period, 44 countries have increasing ASIRs, and 32 countries have decreasing ASMRs, respectively. For instance, in the United States of America, the AAPC of ASIRs significantly decreased by 0.62% and ASMRs significantly decreased by 1.22% from 2000 to 2019, while the AAPC from 2015 to 2019 significantly increased by 0.49% for ASIRs and significantly increased by 0.48% for ASMRs. Conclusion The magnitude of increasing incidence and decreasing mortality of prostate cancer is attenuated in the recent period. Further study is needed to analyze the absolute effect of risk factors, PSA screening and treatment.